2021
DOI: 10.1021/acsabm.1c00402
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Nanofibrous Architectures of Thrombin-Loaded Poly(ethylene oxide) for Faster in Vivo Wound Clotting

Abstract: Wound healing materials to prevent blood loss are crucial during emergency medical treatment because uncontrolled bleeding can lead to patient death. Herein, bioabsorbable fibrous architectures of thrombin-loaded poly­(ethylene oxide)PEO/thrombinare conceptualized and accomplished via electrospinning for faster wound clotting. Membranes with average fiber diameters ranging from 188 to 264 nm are achieved, where the active thrombin is entrapped within the nanofibers. The results of in vitro and in vivo wound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…[ 111 ] Thrombin can be loaded into hemostatic materials by adsorption of positive molecules such as chitosan and mussel‐like structures such as gallic acid and polydopamine. [ 112‐113 ] Whether natural polypeptides, polysaccharides, [ 114‐118 ] or synthetic fiber materials, [ 119‐120 ] thrombin can be easily loaded in. For example, mixing thrombin into electrospinning fiber precursors can easily obtain the hemostatic material.…”
Section: Design Of Bioactive Hydrogel For Hemostasismentioning
confidence: 99%
“…[ 111 ] Thrombin can be loaded into hemostatic materials by adsorption of positive molecules such as chitosan and mussel‐like structures such as gallic acid and polydopamine. [ 112‐113 ] Whether natural polypeptides, polysaccharides, [ 114‐118 ] or synthetic fiber materials, [ 119‐120 ] thrombin can be easily loaded in. For example, mixing thrombin into electrospinning fiber precursors can easily obtain the hemostatic material.…”
Section: Design Of Bioactive Hydrogel For Hemostasismentioning
confidence: 99%
“…Reproduced with permission. [ 23 ] Copyright 2021, American Chemical Society. b) GOx was entrapped into the porous hPB@gellan hydrogel.…”
Section: Design Of Enzyme‐based Biomaterials For Wound Treatmentmentioning
confidence: 99%
“…[ 21 ] While encapsulation usually requires the participation of membranes, and the enzymes are immobilized by strong binding forces that there is almost no leakage of enzymes compared with entrapment. [ 22 ] Mendes et al [ 23 ] prepared a poly (ethylene oxide) (PEO)−thrombin absorbable electrospun nanofiber which thrombin entrapped within the nanofibers (Figure 2B(a)). Nuclear Magnetic Resonance (NMR) spectroscopy specifically showed that there is no chemical reaction occurring between PEO and thrombin, which is the noncovalent coupling concluding from the decrease of the diffusion coefficient of PEO/thrombin.…”
Section: Design Of Enzyme‐based Biomaterials For Wound Treatmentmentioning
confidence: 99%
“…1,2 Its main advantage lies in its powerful ability to catalyze the conversion of brinogen to brin, and it is a key accelerator in the process of blood coagulation. 3,4 However, the major challenge is to maintain the delicate equilibrium between the dosage of thrombin and its safety. 5,6 High concentrations may result in excessive coagulation, leading to thrombosis and serious complications.…”
Section: Introductionmentioning
confidence: 99%